Personal Value Preferences, Threat-Benefit Appraisal of Immigrants and Levels of Social Contact: Looking Through the Lens of the Stereotype Content Model - Walsh, Sophie D.; Tartakovsky, Eugene (Frontiers in Psychology, 2021)
The study examines a model proposing relationships between personal values, positive (i.e. benefits) and negative (i.e. threats) appraisal of immigrants and social contact. Based on a values-attitudes-behavior paradigm, the study extends previous work on personal values and attitudes to immigrants by examining not only negative but also positive appraisal and their connection with social contact with immigrants. Using a representative sample of 1600 adults in the majority population in Israel, results showed that higher preference for anxiety-avoidance values (self-enhancement and conservation) was related to higher levels of perceived threat and lower levels of benefit, while higher preference for anxiety-free values (self-transcendence and openness to change) was related to higher levels of perceived benefits and lower levels of threat. Greater opportunities for contact and perceived benefits and lower levels of threats were related to more social contact. The model showed good fit across the total sample and across four diverse immigrant groups in Israel (diaspora immigrants from the Former Soviet Union, Ethiopia and Western countries and asylum seekers). In line with a Stereotype Content Model, which suggests that group specific stereotypes are related to social structural characteristics of the group, associations between variables differed by group. Results strengthen a theoretical conceptualization that posits an indirect relationship between personal value preferences and behavior through group appraisal. They highlight the importance of comprehensive conceptualizations including both positive and negative appraisal of immigrants, which take into account the way different groups may be appraised by the majority population.